Determinants of Tax Compliance Behavior of Future Taxpayers: Proof of Students in the Cirebon Region Using PLS-SEM - Rizki Indrawan; Amir Hamzah (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Tax compliance among university students is essential for strengthening future tax revenue, yet evidence on its determinants remains limited in Indonesia. Objective: This study aims to examine the effects of tax awareness, tax knowledge, tax system modernization, tax education, tax socialization, and tax ethics on tax compliance behavior among university students in the Cirebon region, Indonesia. Method: This study employed a quantitative research approach involving 260 students from the Faculty of Economics and Business in Cirebon City, Cirebon Regency, and Indramayu. Respondents were selected using purposive sampling based on prior experience with taxation courses. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS to evaluate the relationships among seven research constructs. Results: The findings indicate that tax awareness (β = 0.593, p = 0.001), tax knowledge (β = 0.649, p < 0.001), and tax socialization (β = 0.428, p < 0.001) have significant positive effects on tax compliance behavior. Conversely, tax system modernization (β = −0.280, p < 0.001) and tax education (β = −0.543, p = 0.011) exhibit significant negative effects, suggesting implementation challenges in the student context. Tax ethics does not significantly influence tax compliance behavior (β = 0.067, p = 0.562). The structural model demonstrates excellent explanatory power (R² = 0.981) and high predictive relevance (Q² = 0.895). Conclusion: Tax compliance among university students is mainly influenced by tax awareness, tax knowledge, and tax socialization. The findings provide practical guidance for improving tax education and compliance strategies for future taxpayers.